KORELASI HUBUNGAN ANTARA PENGAWASAN TERHADAP KINERJA PEGAWAI PADA SUKU DINAS PENANGGULANGAN KEBAKARAN DAN PENYELAMATAN KOTA ADMINISTRASI JAKARTA SELATAN - Chrisdiana, Yulvia; Syarkawi, Syarkawi (Ensiklopedia of Journal, 2025)
This study aims to determine the correlation between supervision and employee performance at the Fire and Rescue Sub-Department of the South Jakarta City Administration.  The background to this study was the discovery of problems with employee performance. Lack of supervision results in employees performing their jobs less than optimally. Furthermore, effective supervision is also necessary to ensure employees perform their work in accordance with established procedures.  The approach used in this study was an associative approach. This study employed a descriptive quantitative method. A sample of 103 was selected using the Slovin formula. Data were collected through a validated questionnaire and analyzed using the Classical Assumption Test, Multiple Linear Regression, the t-test, and the Coefficient of Determination. Respondents in this study were employees of the Fire and Rescue Sub-Department of the South Jakarta City Administration, Kebayoran Lama Sector.  The results showed a significant correlation between supervision and employee performance.Keywords: Supervision; Employee Performance; Correlation.